Oral health‐related quality of life impacts are low 27 years after periodontal therapy. (15th June 2020) - Graetz, Christian; Schwalbach, Maike; Seidel, Miriam; Geiken, Antje; Schwendicke, Falk
Abstract: Aim: This pilot study assessed the oral‐health‐related quality of life (OHRQoL) after long‐term periodontal therapy and explored OHRQoL differences along the 2018 Classification of Periodontal Diseases. Methods: Sixty patients were examined before (T0) and after active periodontal therapy (APT/T1) and 32.0 ± 2.9 [range: 27–38] years of supportive periodontal therapy (SPT/T2). Periodontal diagnosis at T0 was assessed according to the 2018 Classification of Periodontal Diseases (stage 1/2/3/4: n = 1/3/44/13; grade n = A/B/C: 0/8/53). OHRQoL at T2 was measured using the Oral Health Impact Profile‐G14 (OHIP‐G14). Patients' Eichner's classification, accumulated tooth loss and treatment outcomes (SSO criteria) were assessed at T2. Generalized linear modelling (GLM) assessed associations between different factors and OHrQoL. Results: Mean OHIP‐G14 sum score was 3.7 ( SD 5.6). There was no statistically significant association between OHIP‐G14 and gender, stage, SSO criteria and tooth loss. OHIP‐G14 was significantly lower in older patients (−0.2[−0.3;0] per year, p = .008), non‐smokers (−5.9[−9.9;‐1.9] p = .003) and former smokers (−7.4[−11.6;‐3.2]; p < .001) versus current smokers, patients with Eichner class A1–B2 versus C2 ( p < .05), sufficient adherence during SPT (−2.3[−4.6;‐0.1], p = .044) versus insufficient ones. Patients with grade B (4.4[1.3;7.4]; p < .005) showed higher OHIP‐G14 than those with grade C. Conclusion: A number of aspects, grounded in the initial diagnosis, the adherence to SPT, the resulting dentition, socio‐demographic and behavioural covariates, were associated with good OHrQoL.